Software FMEA approach based on failure modes database - Baiqiao Huang; Hong Zhang; Minyan Lu (2009 8th International Conference on Reliability, Maintainability and Safety, 2009)
A classification method of software failure modes based on software IPO process is presented. And then two database called general failure modes database (GFMD) and special failure modes database (SFMD) are proposed based on this classification method. Furthermore, a new approach of software FMEA which is based on GFMD and SFMD is presented. This approach which makes the analysis process of FMEA more operable and the failure modes obtained from analysis more comprehensive improves the efficiency of Software FMEA. Meanwhile GFMD and SFMD also offer a platform for the analyzers to accumulate and share their experience. The case study shows that this approach mentioned in this paper is effective in the practice.